Inhibition of the mitochondrial respiratory chain in gills of Rhamdia quelen experimentally infected by Pseudomonas aeruginosa: Interplay with reactive oxygen species - Baldissera M.D. (2017)
© 2017 Elsevier LtdIt has long been recognized that there are several infectious diseases linked to the impairment of enzymatic complexes of the mitochondrial respiratory chain, with consequent production of reactive oxygen species (ROS), that contribute to disease pathogenesis. In this study, we determined whether the inhibition on mitochondrial respiratory chain might be considered a pathway involved in the production of ROS in gills of Rhamdia quelen experimentally infected by P. aeruginosa. The animals were divided into two groups with six fish each: uninfected (the negative control group) and infected (the positive control group). On day 7 post-infection (PI), animals were euthanized and the gills were collected to assess the activities of complexes I-III, II and IV of the respiratory chain, as well as ROS levels. The activities of complexes I-III, II and IV of the respiratory chain in gills decreased, while the ROS levels increased in infected compared to uninfected animals. Moreover, a significant negative correlation was found between enzymatic activity of the complexes I-III and IV related to ROS levels in P. aeruginosa infected animals, corroborating to our hypothesis that inhibition on complexes of respiratory chain leads to ROS formation. Also, microscopic severe gill damage and destruction of primary and secondary lamellae were observed in infected animals, with the presence of hyperplasia, leukocytic infiltration and telangiectasia. In summary, we have demonstrated, for the first time, that experimental infection by P. aeruginosa inhibits the activities of mitochondrial complexes of respiratory chain and, consequently, impairs the cellular energy homeostasis. Moreover, the inhibition on mitochondrial complexes I-III and IV are linked to the ROS production, contributing to disease pathogenesis.